Learning Style Preferences Based on Class and Gender - Farman Farman; Arbain Arbain; Fitriyani Hali (AL-ISHLAH: Jurnal Pendidikan, 2021)
This study aims to identify and describe students' learning style preferences in the mathematics education study program based on class and gender. This research is a type of quantitative research with a descriptive design that describes the percentage of learning style trends in mathematics education students based on class and gender and then draws conclusions on the percentage of learning style preference. The sample of this research was 44 students of the Mathematics Education study program at USN Kolaka. The instrument used in this study was a questionnaire containing 16 questions related to VARK learning styles (Visual, Auditorial, Read/Write, Kinesthetic). The VARK questionnaire instrument used is a standard questionnaire adapted from The VARK Questionnaire Version 7.1. The results showed that students’ learning styles had a multimodal preference(23% bimodal, 27% trimodal, 18% quadmodal).When viewed from class, class A and class B also have a multimodal preference where ARK is the most dominant preference for class A while class B's most dominant preferences are AK and VARK. In terms of gender, women had a multimodal preference (7% bimodal, 33% trimodal and 13% quadmodal) and men had a multimodal preference (31% bimodal, 24% trimodal and 21% quadmodal).